Spiritual Crisis: The Consequences of Forgetting Allah in the Qur’an - Randy Febriananta Primayudha (al-Afkar, Journal For Islamic Studies, 2026)
Forgetfulness is one of the inherent traits of humans. It can occur because information stored in the brain has been replaced or obscured by new information. Forgetting is initially beyond human control because it is located in a part of the brain called the hippocampus, which functions to regulate memory or process information received by human senses. However, it is different from "deliberate forgetting," which is intentionally done to erase something from memory. Islam views forgetfulness as a natural human trait. However, it is different when humans forget their Lord. This happens when they are overpowered by Satan. These devils prevent humans from following the path of Allah, making them negligent in remembering Him and instead following Satan’s ways and their desires. What is even worse is when humans intentionally forget or deny Allah despite the clear warnings sent to them. The purpose of this study is to analyze the terms al-dhikr and al-nasiya and examine the spiritual consequences of forgetting Allah in the Qur’an. The method used in this research is the thematic method (mawdu’i), relying on library-based data sources. The term al-dhikr carries several meanings, including remembrance, prayer, scripture, warning, and lesson. Meanwhile, al-nasiya means forgetfulness or deliberate forgetting. The consequence of forgetting or deliberately ignoring Allah is that on the Day of Judgment, Allah will abandon them to a severe and eternal punishment.